(untitled) (European Journal of Formal Sciences and Engineering, 2022)
This project designed a plant that will process 250 tonnes of raw tomatoes per day. The duration of this production was spread across 24 hours and operated for 300 days in a year, which gave a yield of 17.5 tons of tomato powder per day. From these specifications, the best process route was synthesized. The process route selected involved choosing and sorting the tomatoes, washing, blanching, blending, spray drying (as the drying process), packaging and labeling. Through a series of investigations, the most feasible way to dry tomato powder on an industrial scale proved to be the spray-drying method because the process was very rapid, required low labor cost, and was relatively simple to operate and sustain. The particle size was also easy to control with this technology, making it easy to correlate with product standards. The equipment to be used was then identified which included the machine vision, a spray washer, a water Blancher, an industrial blender, a spray dryer, and a powder packaging machine. Material and energy balance were evaluated around the whole plant. A process flow diagram and basic piping and instrumentation diagram were also computed using engineering software such as Microsoft Visio. From the previous work done, the selected process unit, the spray dryer, was designed with a detailed piping and instrumentation diagram made around it. The site of the plant was resolved, adjacent oriental foods along the Lagos-Ibadan Expressway. It was necessary to site the plant in an area where raw materials can easily be delivered to. The area selected was directly linked to a major highway, the Lagos-Ibadan Expressway, thereby making transport quite affordable. The site layout alongside the plant layout was constructed. The layouts clearly showed the standard flow process.